More flexible and more innovative: the impact of flexible work arrangements on the innovation behavior of knowledge employees - Jiang, Liqun; Pan, Zhiyuan; Luo, Yunshi; Guo, Ziyan; Kou, Deqiang (Frontiers in Psychology, 2023)
There is a definite trend toward the normalization of flexible work arrangements as an efficient means of coping with the dynamic business environment. Existing studies had primarily examined it as a management system, but not fully explored its activation mechanism for employees' proactive work behavior. Based on self-determination theory, this paper constructs a moderated mediation model that empirically examines the influence of a flexible work system on the innovation behavior of knowledge-based employees and obtains the following conclusions: flexible work system can activate innovation behavior of knowledge-based employees, thriving at work plays a partial mediating role and "HRM-opportunity" positively moderates it. The findings not only fill a theoretical research gap but also guide the scientific application of this management system to promote organizational innovation development.